Malkom Khan’s thoughts on modernization of political culture in Iran - Shahriari, Kamyab; Ku Samsu, Ku Hasnita (Macrothink Institute, 2014)
Malkom Khan with his goal in this period of establishing constitutional monarchy gave priority to political culture and criticized the dominant traditional political culture of society. In this period, in addition to paying attention to modernization of political structures and creation of new, modern structures and institutions Malkom Khan also emphasized cultural aspects of society and especially the political culture, by criticizing traditional political culture and attempted to modernize political culture of society. Research result shows that Malkom Khan understood well that the creation of a modern and new political structure must be accompanied by modernization of political culture if the new established structures are to operate effectively and for this purpose he proposed participant political culture instead of subject political culture.